Mucormycosis (black fungus) in COVID-19 patients—Will it be another matter of concern in the midst of the COVID-19 flare-up in Bangladesh? (Journal of Advanced Veterinary and Animal Research, 2021)
Many countries of the world have been combating the new variant of severe acute respiratory syndrome coronavirus 2. Black fungus is an opportunistic foe that may cause fatal infection in immunocompromised and steroid-treated coronavirus disease 2019 (COVID-19) patients. The COVID-19 associated mucormycosis (CAM) is now a serious concern throughout the world, including many Asian countries. Therefore, along with early and accurate diagnostic facilities, special care, and prompt, but coordinated approach are recommended to combat the CAM in patients.J. Adv. Vet. Anim. Res., 8(3): 367-369, September 2021http://doi.org/10.5455/javar.2021.h524